The Â«Wooden StructuresÂ» Discipline Educational and Methodological Complex Development on the Basis Of Informational Intelligent System - Dmytrenko, Tetiana; Dmytrenko, Andrii; Derkach, Tetyana (International Journal of Engineering and Technology, 2018)
This article is devoted to the problem of implementation of computer systems into the educational system, which will help higher educational institutions to increase the level of training professionals.The work analyzes the modern educational informational intelligent systems. It was figured out that they do not completely satisfy the educational process of students of construction specialties. It is proposed to develop a technical task to create an informational intelligent system which could provide teachers and students with effective provision and usage of educational material in the discipline â€œWooden Structuresâ€.The main tasks of the discipline, methods and methodologies of teaching this discipline are analyzed. On the basis of analysis the outline of the educational and methodical complex â€œWooden Structuresâ€ was created.The system offers the possibility of self-testing and self-assessment of knowledge by the student, also the ability to control the process of revising course material.Informational intelligent system of the discipline, which is described in this work, has the principles of training openness and flexibility, individualization and interactivity. The system is implemented on the basis of SCORM standards and the concept of SMART-education.The principles of designing GUI interfaces were used for user interface designing and the most common model for creating the interface for the teacher (editor) and teacher with extended rights (administrator) was chosen.UML-models were used, charts of precedents were created, a database was developed during the systemâ€™s designing.Informational intelligent system of the educational and methodological complex of the discipline â€œWooden structuresâ€ is based on the language of PHP-7, DBMS, Open Server, CMS Wordpress.Â Â